Aspects of chemical reaction and mixed convection in ternary hybrid nanofluid with Marangoni convection and heat source - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
The proposed study examines the effect of inclined magnetic field on a ternary hybrid nanofluid flow that is axisymmetric thermo-solutal Marangoni convective over an infinite disc. Some well-known uses of Marangoni convection include semiconductor production, atomic reactors, crystal growth, fine art mechanisms, melting, thin-film stretching and welding processes. The non-uniform heat generation and viscous dissipation are taken into account. The thermal conductivity and diffusivity coefficient are presumed to vary inversely with linear function of temperature and concentration. The ternary hybrid nanofluid, which consists of silicon dioxide (SiO2), iron oxide (Fe3O4), molybdenum disulfide (MoS2) and ethylene glycol as base liquid, undergoes an energy transition to improve heat transfer. The system of PDEs is transformed into nonlinear ordinary differential equations (ODEs) by using the appropriate transformations. Using the BVP4C method, this problem is numerically solved. The heat and mass phenomena rates on flow behavior are investigated using tables and graphs to address the impact of several physical and flow parameters on velocity, concentration, and thermal profiles. By increasing the Marangoni convection parameter, the surface tension gradient gets stronger, leading to more efficient heat and mass transfer inside the liquid as well as stronger induced flows. As the temperature and concentration profiles decrease, the outcome is a more consistent dispersion of these properties throughout the liquid.
Keywords: Marangoni convection; ternary hybrid nanofluid; chemical reaction; non-uniform heat source; infinite disk